THE ROLE OF POSITIVE AFFECT MEDIATORS ON PERSON ORGANIZATION FIT AND JOB SATISFACTION - Stefanus Rumangkit; Yan Aditiya Pratama (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2020)
This study was to investigate the role of positive affect on the effect of person-organization fit and employment. This study used a quantitative approach. 135 employees who worked in PT. Perusahaan Listrik Negara (PLN) Tarahan, Bandar Lampung was chosen as the respondent in this study. Measurement of the person-organization fit variable was measured by an instrument developed by Kristof (1996). Job satisfaction was measured using the Michigan organization assessment questionnaire (Bowling & Hammond, 2008). Positive affect was measured using the positive & negative affect schedule (PANAS) developed by Watson et al (1988). Data processing and hypothesis testing used moderating regression analysis. The findings in this investigation are: first, P-O fit had a positive and significant effect on employee job satisfaction, second, positive affect did not moderate the relationship between P-O fit and job satisfaction. This was indicated by the interaction variables that are smaller than the significance value.